Suppression of ANT2 by miR-137 Inhibits Prostate Tumorigenesis - Zhang, Heyuan; Chen, Nanhui; Deng, Zhihai; Mai, Yang; Deng, Limin; Chen, Guo; Li, Yutong; Pan, Bin; Zhong, Weifeng (Frontiers in Genetics, 2021)
Prostate cancer (PCa) is a serious disease that affects men's health. To date, no effective and long-lasting treatment option for this condition is available in clinical practice. ANT2 is highly expressed in a variety of hormone-related cancers, but its relationship and regulatory mechanism with PCa are unclear. In this study, we found that ANT2 expression was significantly upregulated in PCa tissues relative to control samples. Genetic knockdown of ANT2 effectively inhibited, while overexpression promoted, proliferation, migration, and invasion of PCa cells. In addition, miR-137 expression was reduced in prostate cancer tissues relative to control tissues. We identified a regulatory site for miR-137 in the 3’-UTR of ANT2 mRNA; luciferase reporter assays indicated that ANT2 is a direct target gene for miR-137. Transfecting cells with miR-137 mimics and/or an ANT2-encoding plasmid revealed that ANT2 promotes proliferation, migration, and invasion of PCa, whereas co-expression of miR-137 mimics inhibited these behaviors. These observations suggest that miR-137 mimics inhibit development of PCa by antagonizing expression of ANT2. Furthermore, tumorigenic assays in nude mice showed that miR-137 inhibitors abolished the inhibitory effect of ANT2 knockdown on PCa tumor growth. Collectively, our findings suggest that ANT2, a target gene of miR-137, is intimately involved in development of PCa, providing new evidence for the mechanism underlying pathogenesis of PCa as well as new options for targeted therapy.